Video compression for panoramic video surveillance systems - Kuzmin, Sergey (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
The article is devoted to the task of video compression for panoramic video surveillance system by means of segmentation of the scene into separate semantically meaningful elements transmitted over communication channel.